Grain brain : the surprising truth about wheat, carbs, and sugar--your brain's silent killers - Perlmutter, David, 1954-; Loberg, Kristin (Little, Brown, and Co., 2013)
The devastating truth about the effects of wheat, sugar, and carbs on the brain, with a 30-day plan to achieve optimum health.